Recessive Dominance: A Descriptive Phenomenological Analysis on the Implications of Education Being a Women-Dominated Field - Fernandez, Harvey Josh; Ramos, Laurence (Universitas Islam Negeri Raden Mas Said Surakarta, 2026)
Studies on women working in male-dominated professions and workplaces that encounter challenges from their colleagues have been existing in recent years. However, through the exploration of the intersection of gender in the learning and the working environment, there are minimal studies that explore the experiences in a women-dominated field, and none in the context of its influence to work dynamics and adjacent implications in the field of education. With this, the study seeks to shed light on the underlying dynamics that shape the academic and professional trajectories of students from Central Luzon State University. The research employed purposive sampling to ensure a diverse range of experiences and perspectives are represented. The data collected were analyzed using thematic analysis and was interpreted using Schütze's notion of Narrative Analysis, to identify recurring patterns, themes, and insights along with a phenomenological approach that shall encompass the variability and peripheral occurrence of the event. Results showed that the phenomenon of education being a women-dominated field paves way for an open atmosphere in the learning and work environment, ready to develop and initiate dialogues into a responsible workflow, as well as take into account deviances into complementary aspects. A women-dominated dynamic promulgated preemptive courses of action sensitive to their coworkers, with an interventionist approach in group works. It is then recommended, as a gateway analysis, for future researchers to explore the other women-dominated field to further identify the workforce with a three-dimensional outlook on gender.